Traditional Gender Role Beliefs and Career Attainment in STEM: A Gendered Story? - Dicke, Anna-Lena; Safavian, Nayssan; Eccles, Jacquelynne S. (Frontiers in Psychology, 2019)
Gender-role beliefs (i.e., beliefs about gender-specific responsibilities) predict one’s educational and occupational aspirations and choices (Eccles et al., 1983; Schoon & Parsons, 2002). Focusing on STEM careers, we aim to examine the extent to which traditional work/family related gender-role beliefs (TGRB) in adolescence predict within and across gender differences in subsequent educational and STEM occupational attainment in adulthood. Using longitudinal data from the Michigan Study of Adolescent and Adult Life Transitions (N=744; 58% female), participants’ educational attainment and their occupations were assessed at age 42. Their occupations were then categorized into three categories: traditional STEM-related careers in the physical sciences, mathematics, engineering, and technology (PMET); life sciences (e.g., health sciences, LS); and non-STEM. For females, TGRB at age 16/18 significantly predicted lower educational attainment as well as a lower likelihood to be in PMET-related occupations—controlling for their own educational attainment. TGRB also predicted a higher likelihood to be in LS-related in comparison to PMET-related occupations. No significant associations were found for males. However, patterns of findings for males were similar to those of females. TGRB also mediated across gender differences in educational and PMET-related occupational attainment. Findings reveal TGRB to be one underlying psychological factor influencing gender disparity in educational and STEM occupational attainment.